LAW ENFORCEMENT AGAINST FOREST FIRE BASED ON PANCASILA IDEOLOGY - Fitri Setiyani Dwiarti (Progressive Law Review, 2022)
Forest fire law enforcement carried out by formal institutions, such as courts and the government shows a formalist, deterministic attitude, the law is understood narrowly and involutively even uprooted from the ideological/philosophical roots of Pancasila. The attitude of law enforcers who often ignore the community's sense of justice with controversial and discriminatory decisions adds to a series of law enforcement problems. local wisdom in Indonesia. This legal paper uses a philosophical approach to examine in depth the ideology of Pancasila in forest fire law enforcement. The sources of material in this paper were obtained from observations, research and literature studies. Laws, especially those relating to the Environment, fail to transform the ideological/philosophical foundation of Pancasila which has become the values ​​and spirit for the long journey of the Indonesian nation. This happens due to the lack of attention to local wisdom and national interests. The theory put forward by Robert B. Seidman, namely "The Law of Non-Transferability of Law" concludes that the law of a nation cannot be taken over, without having to take over the aspects that surround (the socio-cultural aspect) where the law stands. To borrow Satjipto Rahardjo's term, law does not exist in a vacuum, but it exists together with other social sub-systems, within a wider social system. Therefore, a legal culture that is rooted in the noble values ​​of Pancasila and the 1945 Constitution must be accommodated in the preparation of laws and regulations as well as adopting laws that grow and develop in people's lives in forest fire law enforcement to confirm the authenticity of Indonesian law.